2013
DOI: 10.12968/bjmh.2013.2.3.134
|View full text |Cite
|
Sign up to set email alerts
|

Is there a crisis in inpatient mental health care?

Abstract: The standards of care in the NHS are the subject of debate. Frequently, members of the public have complained about poor staff attitudes towards patients and visitors alike and this has generated discussion as to the best way forward for the nursing profession. In mental health, poor standards have been reported on numerous occasions and the first author had firsthand experience of casual nursing attitudes when she visited a friend in an acute inpatient mental health ward. This article uses her anecdotal accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
3
1
0
Order By: Relevance
“…Rooks and Mutsatsa, 2013;Happell et al, 2011). The current study supports these findings as participants felt that that caring for physical health needs was something that they had found difficult to manage upon first qualifying.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Rooks and Mutsatsa, 2013;Happell et al, 2011). The current study supports these findings as participants felt that that caring for physical health needs was something that they had found difficult to manage upon first qualifying.…”
Section: Discussionsupporting
confidence: 77%
“…The findings reported in this paper are similar to previous studies (i.e. Rooks and Mutsatsa, 2013;Hardy et al, 2011;Baker et al, 2012) that have identified deficits in the preparation of mental health nurses. In this regard, the findings are unremarkable.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations